Membangun Ekosistem Kewirausaha di Kalangan Masyakarat Desa - Hapsari Shinta Citra Puspita Dewi; Nurhasan, Nurhasan; Erta, Erta (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Village entrepreneurship is an initiative designed to stimulate regional economic growth by accelerating the development of rural areas, which have long been perceived as slow, less productive, and lagging behind urban centers. The creation of entrepreneurial villages offers a concrete strategy to enhance community productivity because it encourages all components of the village government, residents, and local institutions to participate in structured and collaborative entrepreneurial activities. Such villages are expected to generate new economic opportunities, strengthen local industries, and increase community independence. However, initial observations from this Community Service program show that partner villages still face significant barriers, including limited land area, geographical remoteness, and inadequate human and natural resources. Many peripheral villages have not yet utilized digital technology effectively, making it difficult to expand markets or access broader economic networks. In addition, challenges related to financial access, limited talent development, socio-cultural constraints, and weak market infrastructure continue to hinder economic progress. These conditions demonstrate the urgent need for strategic assistance, capacity-building programs, and stronger support systems to help villages transform into sustainable entrepreneurial ecosystems capable of contributing to long-term regional development.